PENGARUH UKURAN PERUSAHAAN, PERTUMBUHAN PERUSAHAAN, KEBIJAKAN DEVIDEN, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN INDUSTRI MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014 – 2017) - Irsad, Moch.; Sudarsi, Sri (Proceeding SENDI_U, 2020)
The objective of the study is to examine the effect of Firm Size, Growth, Devidend Policy, andProfitability to Firm Value in an industrial manufacturing company that go public on the Indonesian StockExchange. The sampling method inthis study using purposive sampling method with the study period of 2014 to2017. The data used in this research is data from manufacturing companies that meet the selection criteria. Theanalytical method used in this study is multiple regresion analysis.The multiple regression shows that Firm Size,Devidend Policy, and Profitability have significant positive effect on Firm Value, while Growth haven’tsignificant positive effect on Firm Value. Adjusted R Square value of 0,848 can illustrate that the dependentvariable is explained by the independent variable variabelitas for 84,8%, while 15,2% are influenced by theother variables.